Pengaruh Sistem Pertanaman Terhadap Pertumbuhan, Produktivitas, dan Viabilitas Benih Pasca Simpan Beberapa Genotipe Sorgum - Siregar, Syahanda Riswandi; Pramono, Eko; Kamal, Muhammad; Hadi, M. Syamsoel (Journal Galung Tropika, 2020)
The sorghum-cassava intercropping system is a solution to the limited land for planting sorghum in Lampung Province, which is a cassava production area. The aim of this study was to determine the effect of the cropping system on the growth, production, and vigor of the six months' shelf life of the seeds of five sorghum genotypes. The research was conducted on agricultural land in Karang Endah Village, Jati Agung Subdistrict, South Lampung Regency (5.28° SL 105.27° EL) at 82.3 masl and at the Laboratory of Seed and Plant Breeding, Faculty of Agriculture, University of Lampung. The experiment was arranged factorial in a split-plot and repeated as 2 blocks. The main plot was a cropping system consisting of a monoculture cropping system (p1) and an intercropping system (p2). Subplots consist of five sorghum genotypes consisting of Pahat (g1), GHP-1 (g2), GHP-3 (g3), GHP-5 (g4), GH-33 (g5). The sorghum that is planted intercropping with cassava is between 2 rows of cassava plants with 15 cm spacing in rows. On every two rows of cassava, a row of sorghum is planted. The spacing of cassava is 80 cm x 60 cm. The results showed that the intercropping system affected the number of leaves but showed better results at 71.20 g stover dry weight for GHP-1 and 50.10 SPAD for GH-33 for leaf greenness. The difference in cropping systems affected the productivity of sorghum seeds on seed weight per panicle, namely 31.83 g for GHP-3 which showed the largest yield compared to other genotypes but had no effect on the number of seeds per panicle. The treatment of five sorghum genotypes affected the germination rate by 36.83% / day for GH-33 and total normal germination by 84.50% for GH-33. Strong normal sprouts were 89% found in GH-33 from monoculture crops.